2021
DOI: 10.1007/s00421-021-04857-4
|View full text |Cite
|
Sign up to set email alerts
|

Inducing low energy availability in trained endurance male athletes results in poorer explosive power

Abstract: Purpose Low energy availability in males needs more original research to understand its health and performance consequences. The aim of the study was to induce low energy availability in previously healthy male endurance athletes by reducing energy availability by 25% for 14 consecutive days and measure any potential changes in performance, health, mental state or energy markers. Methods Energy availability was reduced in 12 trained, well-trained and elite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Psychological indicators associated with problematic LEA and REDs are mood disturbances/fluctuations,8 71 72 cognitive dietary restraint,73 drive for thinness,74 75 reduced sleep quality50 76 and perfectionistic tendencies 77. Depressive symptoms and affective disorders,8 78 79 subjectively reported reduced well-being,73 primary or secondary exercise dependence/addiction,80 81 anxiety related to injury and/or recovery, sport-specific issues such as difficulty coping with weight requirements67 76 and the development of EDs1 82 are additional adverse mental health outcomes associated with problematic LEA and REDs. However, we must recognise that the picture is still unclear regarding the dynamics of mental health and DE behaviours according to sex and level of competition,83 as well as in athletes with physical disabilities 84.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological indicators associated with problematic LEA and REDs are mood disturbances/fluctuations,8 71 72 cognitive dietary restraint,73 drive for thinness,74 75 reduced sleep quality50 76 and perfectionistic tendencies 77. Depressive symptoms and affective disorders,8 78 79 subjectively reported reduced well-being,73 primary or secondary exercise dependence/addiction,80 81 anxiety related to injury and/or recovery, sport-specific issues such as difficulty coping with weight requirements67 76 and the development of EDs1 82 are additional adverse mental health outcomes associated with problematic LEA and REDs. However, we must recognise that the picture is still unclear regarding the dynamics of mental health and DE behaviours according to sex and level of competition,83 as well as in athletes with physical disabilities 84.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were no such differences in other performance parameters related to power and speed in this study. Opposing to this, a study reported lower explosive power among male endurance athletes, with no significant difference in agility [ 40 ]. Decrease in performance, particularly in endurance activities, have been related to dietary intake restriction, and male athletes often reported to reduce food intake or under-eat during competitions [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study involved trained male endurance athletes who undertook a stepwise series of 14-day exposures equivalent to 25%, 50% and 75% reduction in their baseline estimated EA, with stages equivalent to overall EA of ~22, 17 and 9 kcal/kg FFM 43. Most other controlled field-based prospective investigations of EA exposure in athletes or active people have involved comparison of a single, severe16 44–49 (eg, 10–15 kcal/kg FFM/day) or moderate50–53 (20-25 kcal/kg FFM/day) restriction of EA compared with ‘adequate’/’high’ EA or energy balance (40–50 kcal/kg FFM/day), with interventions lasting from 3 to 9 days. Other prospective observational studies54–56 have identified self-imposed differences in EA in athletes over periods of 5 days to 12 weeks, enabling differences in health or performance outcomes between LEA exposures to be assessed.…”
Section: Methodsmentioning
confidence: 99%